Analisis Ahli Cakram Asupan Makan dan Cairan Atlet: Studi Awal Pengembangan Media Edukasi Atlet Remaja - Afriani, Yuni; Sari, Siska Puspita; Puspaningtyas, Desty Ervira (Jurnal Gizi, 2022)
Many young athletes have undernourished nutritional status, lack of knowledge, and improperselection of nutritional intake. It has an impact on the success of athletes when conducting games.One of the contributing factors is the suboptimal use of educational media for athletes.Educational media, Cakram is one of the alternative media that needs to be developed and appliedto young athletes. Cakram Asupan Makan dan Cairan Atlet (CAMCA) is an educational mediainnovation that makes it easier for athletes. This study aims to analyze the level of mediaacceptance of Cakram Asupan Makan dan Cairan Atlet (CAMCA) conducted on experts in thefield of Sports Nutrition as a solution to athletes' health independence, especially optimizing thenutritional status of adolescent athletes. This research was a quantitative descriptive study. Thisresearch began with the manufacture and development of cakram by looking at the level ofacceptance of Cakram Asupan Makan dan Cairan Atlet (CAMCA) media by experts in the field ofSports Nutrition. Data were analyzed descriptively. Nutrition education media in the form ofCakram Asupan Makan dan Cairan Atlet (CAMCA) is very interesting media to be developed andapplied to young athletes related to the fulfillment of nutritional intake.Keywords: young athletes; cakram gizi; educational media; athlete performance